Edge Computing and Microservices: Extending Scalability Beyond the Cloud - Venkata Durga Ganesh Nandigam, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The convergence of edge computing and microservices architecture represents a transformative shift in how organizations process and manage distributed data systems. This article explores the limitations of traditional cloud-centric approaches and presents edge computing as a solution to address these challenges. Through a detailed analysis of real-world implementations across various sectors, including autonomous vehicles, smart cities, and industrial automation, the article examines how edge computing integrated with microservices architecture improves system performance, reduces latency, and optimizes resource utilization. The article investigates deployment challenges and security considerations and provides insights into effective monitoring strategies. Furthermore, the article explores emerging technologies and future research directions that will shape the evolution of edge computing and microservices integration.
Keywords: Edge Computing; Microservices Architecture; IoT (Internet of Things); Cloud Infrastructure; Distributed Systems